JANGER BANYUWANGI: LANGUAGE AS A MEDIUM OF LOCAL CULTURE - Ahmad Sulthoni; Dhalia Soetopo (University of Kuningan, 2026)
Janger is one of Banyuwangi's traditional performing arts that displays a combination of music, dance, dialogue, and humor as a form of cultural expression of the Osing people. In practice, language functions not only as a means of communication between actors and audiences, but also as the main medium for conveying moral, social, and local wisdom values that are inherited across generations. This study aims to examine the function of language in Janger as a representation of the cultural identity of the Osing people, especially in the midst of social changes due to modernization and tourism. The research method used is qualitative with a literature study approach and in-depth interviews with several Janger art actors and local cultural figures. The results of the study show that the use of the Osing language in Janger has a central role in strengthening the identity and pride of the community. However, in its development, there has been adaptation through the insertion of Javanese and Indonesian languages so that the message is easier to receive to a wider audience, including tourists. This adaptation reflects an effort to maintain the show's relevance without losing its traditional meaning. The language in Janger has proven to have a dual function: as entertainment as well as an educational and reflective medium that strengthens social solidarity. Thus, Janger becomes an arena where the Osing language transforms, maintaining the roots of tradition, but also being open to change to answer the challenges of the times.